POLAR MOTION AT SEASONAL FREQUENCIES - Hopfner J. (My University, 1996)
Studying the planetary-dynamic behaviour of the Earth connected with geophysical processes as sources of excitation is of particular importance. In order to make a contribution concerning seasonal influences of near-surface geophysical processes on polar motion and Earth rotation, numerical investigations based on a time series of Earth Rotation Parameters and Atmospheric Angular Momentum parameters from 1976 to 1987 were performed. Atmospheric Angular Momentum changes are the dominant cause of polar motion and length-of-day variation at seasonal frequencies. Since there is another excitation source, the problem is to be considered such that the total excitation portion is composed of atmospheric and non-atmospheric portions. Particularly in polar motion, the paper deals with the separation of these portions for the seasonal constituents and presents interesting information about their character.